2012
DOI: 10.3354/meps09611
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Hediste diversicolor (Polychaeta, Nereididae) from the northwestern Mediterranean as revealed by DNA inter-simple sequence repeat (ISSR) markers

Abstract: The polychaete Hediste diversicolor is characterised by a high degree of genetic structure among populations. The genetic differentiation has been related to the presence of cryptic species, corresponding to Atlantic and Mediterranean lineages whose divergence may have been driven by vicariance and/or selection. In the present study we used DNA inter-simple sequence repeat (ISSR) markers to validate the genetic structure in 9 populations from the northwestern Mediterranean. We also analysed patterns of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The nuclear molecular markers here employed, ISSRs, were used in many studies to evaluate the population structure of marine invertebrates, including limpets (Casu et al, 2005(Casu et al, , 2006Cossu et al, 2012;de Aranzamendi et al, 2008;Fernández et al, 2011;Hou et al, 2006;Maltagliati et al, 2004;Pannacciulli et al, 2009;Varela et al, 2007). Genetic differences among closely related species of Nacella were successfully revealed using ISSRs but not using mitochondrial coding genes COI and Cyt b (de Aranzamendi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear molecular markers here employed, ISSRs, were used in many studies to evaluate the population structure of marine invertebrates, including limpets (Casu et al, 2005(Casu et al, , 2006Cossu et al, 2012;de Aranzamendi et al, 2008;Fernández et al, 2011;Hou et al, 2006;Maltagliati et al, 2004;Pannacciulli et al, 2009;Varela et al, 2007). Genetic differences among closely related species of Nacella were successfully revealed using ISSRs but not using mitochondrial coding genes COI and Cyt b (de Aranzamendi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[34]). Because not all five markers performed equally well for each species, the most informative 2–3 markers per species were chosen for subsequent brood screening.…”
Section: Methodsmentioning
confidence: 99%
“…Is Namalycastis abiuma restricted to its type-locality? Alves et al Sato and Nakashima, 2003;Audzijonyte et al, 2008;Cossu et al, 2012;Teixeira et al, 2022). Considering Namanereidinae species, Magesh et al (2014b) found evidence for an incipient speciation process within N. abiuma species group using morphological and molecular data.…”
Section: Namanereidinaementioning
confidence: 99%